NASAL ENDOSCOPIC FINDINGS IN CHRONIC NASAL OBSTRUCTION - Mohammed Sahib Salman; Harith AbdulJabbar Ayoob; Raed Sami Tuama Aljuboori (Scholar Express Journals, 2022)
This study aims to evaluate the results obtained from Nasal endoscopic findings in chronic nasal obstruction and comparison with another method where 100 patients were collected and distributed based on the CT scan and nasal endoscopic finding as the statistical analysis program was relied upon spss soft 22 and program soft EXCEL Ages are categorized into four categories: )30-34(,)35-39(,)40-44(,)45-50 and we concloude in last of study in otolaryngology, NE is the gold standard for diagnosing diseases of the nose, paranasal sinuses and nasopharynx where many minimally invasive interventions are also performed, the effectiveness of which sometimes exceeds that of traditional ENT operations. Therefore, in many modern clinics
Keywords: NE; CT; obstruction; ENT